EVALUASI FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN PENYELESAIAN PROYEK KONSTRUKSI DENGAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS (AHP) DI KOTA PADANG - Lisa Rahmi; firman firman; Gesit Tabrani (Universitas Negeri Padang, 2019)
This study aims to find out, what are the factors that cause delays in project development in Padang City. The population in this study were several contractors registered as members of GAPENSI Kota Padang. The number of samples is the majority contractor, consisting of 3 intermediate contractors and 5 small contractors. The method used is a cause and effect diagram (fishbone) and Analytical Hierarchy Process (AHP). The results of this study are the main factors that cause delays in the repair of construction projects, namely: (1) delays caused by specifications / design changes with a value of 0.1265, (2) weather and natural disasters with a value of 0.1144, (3 )) error in choosing the construction method with a weight value of 0.0912.Keywords: Construction Project Delay Factors, Cause-Effect Diagram (Fish Bone), Analytical Hierarchy process (AHP).